2009
DOI: 10.1111/j.1365-2222.2009.03342.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wheat and rye flour solutions for skin prick testing: a multi‐centre study (Stad 1)

Abstract: There is a wide variability of SPT solutions for wheat and rye flour from different producers, mainly with respect to sensitivities, negative predictive values, and test efficiencies. Improvement and standardization of SPT solutions used for the diagnosis of baker's asthma are highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 24 publications
3
27
0
3
Order By: Relevance
“…Tests were performed in duplicate as described recently . A wheal diameter of at least 3 mm in at least one of both tests was defined as positive as it has been shown that small wheal diameters demonstrate the highest test efficiencies (van Kampen et al 2009). …”
Section: Skin Prick Test (Spt)mentioning
confidence: 99%
“…Tests were performed in duplicate as described recently . A wheal diameter of at least 3 mm in at least one of both tests was defined as positive as it has been shown that small wheal diameters demonstrate the highest test efficiencies (van Kampen et al 2009). …”
Section: Skin Prick Test (Spt)mentioning
confidence: 99%
“…The bronchial response to an occupational agent may vary according to its physicochemical characteristics [52][53][54]. Nebulising saline solutions of water-soluble HMW agents has limitations since standardised solutions of occupational agents are lacking (except for latex), and some relevant allergens may not be water soluble [55,56].…”
Section: Methods For Delivering Occupational Agentsmentioning
confidence: 99%
“…Nevertheless, it has to be considered that all these evaluations are in fl uenced by the selected 'gold standard' which is in our case the self-reported asthmatic symptoms. Whereas predictive values depend largely on the prevalence rates of cases under study, sensitivity and speci fi city are presumably inherent characteristics of the test (Feinstein 1975 ;van Kampen et al 2009 ) . Thus, we used the Youden Index, considering sensitivity and speci fi city equally to de fi ne the optimal positivity criterion (cut-off level) for each parameter, because this index should be independent of selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate speci fi c parameters in EBC and IS as suitable diagnostic parameter for the detection of asthmatic symptoms (AS), the self-reported current asthmatic symptoms were taken as the gold standard to calculate sensitivities, speci fi cities, positive predictive values (PPV), negative predictive values (NPV), and test ef fi ciencies. For the evaluation of a parameter, the mediator or cell concentration leading to the maximum Youden Index (sensitivity + speci fi city − 1) was chosen as the optimal cut-off level (as described by van Kampen et al 2009 ) . The data were analyzed by using GraphPad Prism version 5.01 for Windows (GraphPad Software, San Diego, CA).…”
Section: Discussionmentioning
confidence: 99%